2014
DOI: 10.1080/08941920.2013.861564
|View full text |Cite
|
Sign up to set email alerts
|

African Inland Fisheries: Experiences with Co-Management and Policies of Decentralization

Abstract: Most countries in Africa have promoted some form of decentralized fisheries management either as discrete co-management projects or as a component of broader decentralization processes that cut across other sectors. These initiatives were shaped by an international policy narrative that emphasises participation in decision making and development. A review of fisheries decentralization experiences in Cameroon, Niger, Nigeria, and Malawi reveals marked differences in purpose, strategy, and performance. In genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…As pointed out by Barendse, Roux, Currie, Wilson, and Fabricius (2016), one limiting external factor is the government’s inadequate implementation capacity so that local governance institutions have narrow capacity to develop natural resource stewardship. This holds for wildlife as well as for fishery management (Cox, Wilson, & Pavlovich, 2016; Lewins et al., 2014; Ngwira, Kolawole, & Mbaiwa, 2013; Nkhata, Breen, & Abacar, 2009; Nunan, 2006; Sutton & Rudd, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out by Barendse, Roux, Currie, Wilson, and Fabricius (2016), one limiting external factor is the government’s inadequate implementation capacity so that local governance institutions have narrow capacity to develop natural resource stewardship. This holds for wildlife as well as for fishery management (Cox, Wilson, & Pavlovich, 2016; Lewins et al., 2014; Ngwira, Kolawole, & Mbaiwa, 2013; Nkhata, Breen, & Abacar, 2009; Nunan, 2006; Sutton & Rudd, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the popularity of the philosophy, the overall impact of CBNRM remains unclear (Lewins et al., 2014; Riehl, Zerriffi, & Naidoo, 2015; Silva & Mosimane, 2012). Impacts can be measured at multiple scales; at the national level, CBNRM programs appear to be having a positive impact throughout sub-Saharan Africa.…”
mentioning
confidence: 99%
“…The previous section has already made it clear that besides the BVC Chair, village chiefs are holding a powerful position in the Elephant Marsh Fishery; see also Lewins et al (2014) and Russell and Dobson (2011). Our interviews with fishers, village chiefs, and BVC Chairs at the Elephant Marsh revealed four roles of chiefs in the small-scale fishery, as follows: (i) A BVC Chair cannot accept a new fisher without first asking for consent from the village chief.…”
Section: Power Relations Between the Village Chief And Bvc Chair Are mentioning
confidence: 99%
“…The concept of BVCs was introduced in Malawi in 1991 as a government initiative under the Participatory Fisheries Management Programme (PFMP) in response to declining fish catches at Lake Malombe and the Upper Shire River (Lewins et al 2014). Since then BVCs have been adopted at the national level and supported by the National Fisheries and Aquaculture Policy (NFAP) (Government of Malawi 2001) as a participatory link between the Department of Fisheries (DoF) and the fishing communities.…”
mentioning
confidence: 99%
“…About 15% of the respondents pushed the responsibility to the government, while 8% suggested that they pay through tax. The ecosystem management approach follows top-down in Malawi, where the government creates rules and imposes them on the local population ( Lewins et al., 2013 ). However, this approach has faced strong resistance in its implementation ( Wilson et al., 2010 ), as reflected in the negative WTP responses.…”
Section: Discussionmentioning
confidence: 99%